+0  
 
0
155
1
avatar+4 

If 𝑥 + 𝑦 = 5 and 𝑥𝑦 = −3, then 𝑥2 + 𝑦2 is equal to

Skylion  Jun 10, 2017
Sort: 

1+0 Answers

 #1
avatar+26275 
+1

We have  \((x+y)^2=x^2+y^2+2xy\)

 

So  \(x^2+y^2=(x+y)^2-2xy\)

 

Here:  \(x^2+y^2=5^2-2(-3)\text{ ... or ... }x^2+y^2=25+6\rightarrow31\)

 

 

.

Alan  Jun 10, 2017

22 Online Users

avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details